GE_GERICHTE P/17491/2013 vom 3. Januar 2023 - GE Cour de justice (2023)
ABUS DE CONFIANCE;ESCROQUERIE;GESTION DÉLOYALE;FAUX DANS LES CERTIFICATS;CRÉANCE;ALLOCATION AU LÉSÉ | CP.138; CP.158; CP.251; CP.146; CP.71.al1; CP.73.al1; CPP.268.al1.leta